Supply curves of electricity-based gaseous fuels in the MENA region. (December 2021) - Lux, Benjamin; Gegenheimer, Johanna; Franke, Katja; Sensfuß, Frank; Pfluger, Benjamin
Highlights: Design of integrated e-fuel production chains for the MENA region. Electricity-based hydrogen and methane supply curves for MENA in 2030 and 2050. Integrated optimization of electricity generation and e-fuel production. Comparison of hydrogen production costs in MENA and Europe. Abstract: The utilization of electricity-based fuels (e-fuels) is a potential strategy component for achieving greenhouse gas neutrality in the European Union (EU). As renewable electricity production sites in the EU itself might be scarce and relatively expensive, importing e-fuels from the Middle East and North Africa (MENA) could be a complementary and cost-efficient option. Using the energy system model Enertile, supply curves for hydrogen and synthetic methane in the MENA region are determined for the years 2030 and 2050 to evaluate this import option techno-economically. The model optimizes investments in renewable electricity production, e-fuel production chains, and local electricity transport infrastructures. Analyses of renewable electricity generation potentials show that the MENA region in particular has large low-cost solar power potentials. Optimization results in Enertile show for a weighted average cost of capital of 7% that substantial hydrogen production starts above 100 €/MWhH2 in 2030 and above 70 €/MWhH2 in 2050. Substantial synthetic methane production in the model results starts above 170 €/MWhCH4 in 2030 and above 120 €/MWhCH4 in 2050. The most important cost component in both fuel production routes is electricity. Taking into account transport cost surcharges, in Europe synthetic methane from MENA is available above 180 €/MWhCH4 in 2030 and above 130 €/MWhCH4 in 2050. Hydrogen exports from MENA to Europe cost above 120 €/MWhH2 in 2030 and above 90 €/MWhH2 in 2050. If exported to Europe, both e-fuels are more expensive to produce and transport in liquefied form than in gaseous form. A comparison of European hydrogen supply curves with hydrogen imports from MENA for 2050 reveals that imports can only be economically efficient if the two following conditions are met: Firstly, similar interest rates prevail in the EU and MENA; secondly, hydrogen transport costs converge at the cheap end of the range in the current literature. Apart from this, a shortage of land for renewable electricity generation in Europe may lead to hydrogen imports from MENA. This analysis is intended to assist in guiding European industrial and energy policy, planning import infrastructure needs, and providing an analytical framework for project developers in the MENA region.